2014
DOI: 10.1111/etap.12061
|View full text |Cite
|
Sign up to set email alerts
|

On the Frontiers: The Implications of Social Entrepreneurship for International Entrepreneurship

Abstract: We explore how social entrepreneurship (SE) research extends the field of international entrepreneurship (IE) to affect global sustainable well–being. Well–being is a multidimensional concept that includes financial, social, and environmental wealth creation. Much of IE research thus far has been based primarily on assumptions of economic opportunity recognition, evaluation, and exploitation. We use the SE perspectives of blended value and international governance to revise the definition, assumptions, and bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(109 citation statements)
references
References 60 publications
1
99
0
9
Order By: Relevance
“…Recently, some social entrepreneurial opportunities have been found to be of international nature, such as entrepreneurial opportunities tackling environmental issues, e.g., climate change and energy depletion or social issues, e.g., global poverty gap (Zahra et al 2008;Zahra et al 2014;Alvarez and Barney 2014). There is an emerging phenomenon of entrepreneurial activities achieving both internationalization and socially oriented value creation.…”
Section: Emerging Phenomenon Of International Social Entrepreneurshipmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, some social entrepreneurial opportunities have been found to be of international nature, such as entrepreneurial opportunities tackling environmental issues, e.g., climate change and energy depletion or social issues, e.g., global poverty gap (Zahra et al 2008;Zahra et al 2014;Alvarez and Barney 2014). There is an emerging phenomenon of entrepreneurial activities achieving both internationalization and socially oriented value creation.…”
Section: Emerging Phenomenon Of International Social Entrepreneurshipmentioning
confidence: 99%
“…There is an emerging phenomenon of entrepreneurial activities achieving both internationalization and socially oriented value creation. Entrepreneurial activities with social missions and international missions and operations, focusing on blended value creation, social change, and environmental sustainability, are defined as international social entrepreneurship (ISE) (Zahra et al 2014;Munoz 2010). Social ventures with international missions and operations are called ISVs (Zahra et al 2008;Chen 2012).…”
Section: Emerging Phenomenon Of International Social Entrepreneurshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the social aspect, previous studies have indicated that an SE focuses on obtaining entrepreneurial rents, while simultaneously improving social and environmental conditions both locally and globally (Cohen and Winn, 2007;Dean and McMullen, 2007;Zahra et al, 2014). Corner and Ho (2010) studied the identification of opportunity in the social entrepreneurship literature and observed that SE practitioners tend to identify social need and generate prospective ideas for resolving it.…”
Section: Performance Of An Sementioning
confidence: 99%